The effect of post space irrigation protocol and adhesive strategy on push out bond strength to radicular dentin: A network meta-analysis - Fatemeh Pournaghi Azar; Elaheh Javari; Haleh Valizadeh; Hossein Hosseinifard (Journal of Research in Clinical Medicine)
Introduction: Establishing an effective bond with root dentin remains a complex task, with bond strength diminishing from the coronal to the apical third as a result of reduced dentinal tubule density and limited access to light curing instruments. This network meta-analysis studied the effect of cement and irrigation protocols on push out bond strength to radicular dentin. Methods: In vitro studies evaluating self- etch, self-adhesive, total etch resin cements, and ethylenediaminetetraacetic acid (EDTA), sodium hypochlorite (NaOCl), distilled water, chlorhexidine (CHX) irrigants were included. A network meta-analysis was performed using a random effect model. The efficacy of the different irrigation and adhesion protocols was ranked using P scores. A comprehensive search was carried out in the "Web of Science", "PubMed", "Scopus", and "Embase" databases by October, 2022. Results: It was shown that the irrigation protocol and adhesive strategy with the greatest chance of producing higher bond strength was EDTA+NaOCL/Total etch (push out MD 6.69 MPa, P=0.95) proceeded with CHX/self -adhesive (push out MD 3.70 MPa, P=0.77) compared to Distilled water/Total etch as the control group. Conclusion: Network meta-analyses identified EDTA+NaOCL/Total etch resin cement and self-adhesive cements/CHX as the most efficient protocols for increasing push out bond strength to radicular dentin.